Eco-nic Firestarter / Nurul Atikah J Effendy and Ku Mahiran T Nor - J Effendy, Nurul Atikah; T Nor, Ku Mahiran (2020)
ECO-NIC FIRESTARTER is a natural fire starting product carefully designated for indoor and outdoor activities like cooking, generating light and heat, signaling and also for incineration of waste. We make sure that Eco-nic Firestarter is an eco-friendly product as it aligns with 3R concept (Reduce, Reuse and Recycle). To guarantee the quality of environment is always in a good care, combination of cow dung and recyclable materials are used as the main ingredients of the product. Our product is 98% made of organic components. Their main ingredients are cow dung, coconut husk, effective microbe (EM) and citronella which are safe, affordable and free from chemicals. We believe our product will become staple household goods as it can be used for various activities, marketable to every group of people and costs a lot cheaper than existing products today.